Generation of anti-hirudin antibodies in heparin-induced thrombocytopenic patients treated with r-hirudin - Song, Xuehong; Huhle, Günter; Wang, Lianchun; Hoffmann, Ursula; Harenberg, Job (Circulation, 1999)
Background—Hirudin is a small protein with strong thrombin inhibition that may be antigenic. The generation and disappearance of anti-hirudin antibodies were investigated in patients with heparin-induced thrombocytopenia who were treated with recombinant hirudin (r-hirudin) for ≥5 days. - - Methods and Results—The IgA, IgE, IgG, and IgM isotypes of anti-hirudin antibodies were determined by ELISA before and after the start of r-hirudin therapy. A total of 56% of patients (13 of 23) developed ≥1 antibody isotype during therapy. No IgE antibodies were generated. IgA, IgG, and IgM antibodies were detected in 30% (7 of 23), 52% (12 of 23), and 17% (4 of 23) of patients, respectively. Four patients generated only IgG, 2 patients developed either IgM or IgG and IgM, 5 patients IgG and IgA, and 2 patients IgG, IgM, and IgA antibodies. IgM antibodies disappeared within 8 days of the cessation of r-hirudin. IgA and IgG antibodies disappeared within 1 year in all but 1 patient. Binding of purified IgG to r-hirudin in IgG antibody-positive patients (n=7) was demonstrated by competitive ELISA for r-hirudin. Of the 7 IgG antibody samples, 1 each neutralized or enhanced the anticoagulant activity of r-hirudin. - - Conclusions—R-hirudin may be antigenic in patients with heparin-induced thrombocytopenia. More comprehensive investigations will be required to determine the biological relevance of this and to establish the antibody-generation pattern in other diseases.
Gesehen am 05.05.2022